2013
DOI: 10.1371/journal.pone.0056825
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsense Mutation in the Acid α-Glucosidase Gene Causes Pompe Disease in Finnish and Swedish Lapphunds

Abstract: Pompe disease is a recessively inherited and often fatal disorder caused by the deficiency of acid α-glucosidase, an enzyme encoded by the GAA gene and needed to break down glycogen in lysosomes. This glycogen storage disease type II has been reported also in Swedish Lapphund dogs. Here we describe the genetic defect in canine Pompe disease and show that three related breeds from Scandinavia carry the same mutation. The affected dogs are homozygous for the GAA c.2237G>A mutation leading to a premature stop cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Se han encontrado numerosos cambios en la secuencia, de los cuales 75% son patógenos, lo cual puede afectar el mecanismo de corte y empalme de los exones, la estabilidad del ARN mensajero y biosíntesis de la proteína ocasionando que la enzima no actue. Deseamos resaltar que en el caso del paciente estudiado, se ha encontrado una variante que no ha sido reportada en la literatura, por sus características de homocigocidad (8). Este diagnóstico molecular puede tener dificultades en la interpretación.…”
Section: Discussionunclassified
“…Se han encontrado numerosos cambios en la secuencia, de los cuales 75% son patógenos, lo cual puede afectar el mecanismo de corte y empalme de los exones, la estabilidad del ARN mensajero y biosíntesis de la proteína ocasionando que la enzima no actue. Deseamos resaltar que en el caso del paciente estudiado, se ha encontrado una variante que no ha sido reportada en la literatura, por sus características de homocigocidad (8). Este diagnóstico molecular puede tener dificultades en la interpretación.…”
Section: Discussionunclassified
“…The underlying genetic defects have been identified in Brahman and Shorthorn cattle breeds in Australia, in quails (AMD quails), and Finnish and Swedish Lapphunds. Curiously, the two Scandinavian dog breeds, which share a common origin and physical appearance, have been recently shown (Seppala et al, 2013) to contain a frameshift mutation similar to that found in patients with the infantile form of the disease (the finding points to a "hot spot" in the GAA gene). The presence of residual GAA activity in quails (due to the expression of other alpha-glucosidases) accounts for the milder form of the disease, which mimics human childhood or adult forms without cardiac dysfunction; the birds show progressive muscle weakness, difficulty in lifting their wings or turning from the supine position.…”
Section: Models Of Pompe Diseasementioning
confidence: 90%
“…Glycogen accumulations consisting of membrane bound vacuoles were present in the heart, skeletal, and smooth muscle. The genetic basis was a c.2237G>A change corresponding to the nonsense mutation p.W746* in the acid α-glucosidase gene [7]. …”
Section: Potential For Clinical Development Of Gene Therapy In Pompe mentioning
confidence: 99%